Class III peroxidases PRX01, PRX44, and PRX73 potentially target extensins during root hair growth in Arabidopsis thaliana - Marzol, Eliana (2020)
Root hair cells are important sensors of soil conditions. Expanding several hundred times their original size, root hairs grow towards and absorb water-soluble nutrients. This rapid growth is oscillatory and is mediated by continuous remodelling of the cell wall. Root hair cell walls contain polysaccharides and hydroxyproline-rich glycoproteins including extensins (EXTs). Class-III peroxidases (PRXs) are secreted into the apoplastic space and are thought to trigger either cell wall loosening, mediated by oxygen radical species, or polymerization of cell wall components, including the Tyr-mediated assembly of EXT networks (EXT-PRXs). The precise role of these EXT-PRXs is unknown. Using genetic, biochemical, and modeling approaches, we identified and characterized three root hair-specific putative EXT-PRXs, PRX01, PRX44, and PRX73. The triple mutant prx01,44,73 and the PRX44 and PRX73 overexpressors had opposite phenotypes with respect to root hair growth, peroxidase activity and ROS production with a clear impact on cell wall thickness. Modeling and docking calculations suggested that these three putative EXT-PRXs may interact with non-O-glycosylated sections of EXT peptides that reduce the Tyr-to-Tyr intra-chain distances in EXT aggregates and thereby may enhance Tyr crosslinking. These results suggest that these three putative EXT-PRXs control cell wall properties during the polar expansion of root hair cells.